Assessing Clinical Improvement in School-Based Treatment for Social Anxiety Disorder: Agreement between Adolescents, Parents, and Independent Evaluators - Fox, Jeremy K. (Child Psychiatry Hum Dev, 2017)
The Clinical Global Impressions of Improvement (CGI-I) scale is widely used in clinical trials to monitor clinically meaningful change during treatment. Although it is standard practice in research to have independent evaluators (IEs) complete the CGI-I, this approach is not practical in school and community settings. Few studies have explored the potential utility of other informants, such as youth and parents. Therefore, this study aimed to investigate agreement between IEs and both adolescents and parents in CGI-I improvement ratings in the context of a randomized controlled trial of cognitive-behavioral therapy for social anxiety disorder, as delivered by psychologists and school counselors. Multilevel growth models indicated that IEs were generally more conservative in their ratings of positive treatment response across time and treatment conditions, though greater agreement was observed between parents and IEs by post-intervention and five-month follow-up. Possible explanations for these findings and suggestions for alternative approaches are discussed.